Analisis Kolaborasi Pemerintah Pusat dan Daerah dalam Penanganan Banjir melalui Sistem Drainase di Kota Medan - Meiyolanda Sormin; Victor Lumbanraja (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Flooding is a problem that continues to occur in Medan City due to suboptimal drainage conditions, river sedimentation, massive development, and reduced water catchment land. Flood management cannot be carried out by one agency alone because it involves the authority of the central government, provincial governments, and city governments. Therefore, collaboration between governments is needed in handling floods through drainage systems. However, in its implementation, various obstacles are still found, such as weak coordination, differences in priorities between agencies, and the absence of a strongly integrated collaboration mechanism. This study aims to analyze the collaboration of the central and regional governments in handling floods through the drainage system in Medan City and to find out the factors that hinder this collaboration.   This study uses the collaborative governance theory of Ansell and Gash (2008) with indicators of initial conditions, facilitative leadership, institutional design, and collaborative processes. The research method used is a qualitative method. The data collection technique was carried out through interviews, observations, and documentation with informants from the Medan City Water Resources, Highways, and Construction Development, the Public Works and Spatial Planning Office of North Sumatra Province, the Sumatra II River Area Center, and flood-affected communities.   The results of the study show that collaboration between agencies has basically run through formal and informal communication, division of tasks according to authority, and the implementation of river and drainage normalization. The collaboration also resulted in several initial achievements, such as increasing water holding capacity and faster inundation in some areas. However, collaboration has not run optimally due to the absence of a joint Standard Operating Procedure (SOP) and Decree (SK), personnel change, weak documentation and knowledge transfer, differences in priorities between agencies, and low community participation. In addition, the results of flood management have not been fully felt by the community because floods still occur during heavy rains. Therefore, institutional strengthening, coordination, and community participation are needed so that collaboration in flood management can run more effectively and sustainably.